Preparation of charged mosaic membrane of sodium polystyrene sulfonate and poly(4‐vinyl pyridine) by conjugate electrospinning. Issue 17 (3rd April 2014) - Chen, Yulu; Cui, Yimeng; Jia, Yuanshan; Zhan, Kan; Zhang, Hui; Chen, Guoxia; Yang, Yadong; Wu, Min; Ni, Henmei
ABSTRACT Conjugate electrospinning of two nozzles with opposite charges was used for the fabrication of charged mosaic membrane (CM membrane). Sodium polystyrene sulfonate (PNaSS) and poly(4‐vinyl pyridine) (P4VP) were selected as anionic and cationic exchange elements, respectively. Polyvinyl alcohol was used as the common matrix for the enhancement of mechanical properties by formaldehyde crosslinking. Scanning electron microscope (SEM), transmission electron microscope (TEM), and tensile testing for nanofiber were used for the characterizations of CM membrane. Using the conjugate electrospinning, a simple equation was established to predict the mean diameters of nanofibers. It was proved that the calculated diameters fit well with the experimental data using electrospinning parameters such as concentration of spun solution, collecting speed, rate of solution supply, and distance of two nozzles. TEM picture showed a PNaSS nanofiber was incorporated with a P4VP nanofiber. However, SEM photo indicated that the alignment of composite nanofibers in CM membrane was greatly affected by the concentration of polyelectrolyte. As the concentration of PNaSS increased, the alignment degree decreased. After crosslinking with formaldehyde for 20 h, the tensile strength and Young's modulus of CM membrane reached 11.3 and 24.8 MPa, respectively. The water content and water insolubility of CM membrane were also investigated. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40716.